Alcohol-related victimisation: Differences between sexual minorities and heterosexuals in an Australian national sample - Tait, Robert (Wiley-Blackwell Publishing Ltd., 2015)
Introduction and Aims - Alcohol-related violence and other types of victimisation are prevalent, but unevenly distributed across the population. The study investigated the relationship between alcohol-related victimisation and sexual orientation (heterosexual, homosexual, bisexual, other) in a national sample. Design and Methods - The study used cross-sectional data from the 2010 Australian National Drug Strategy Household Survey. Logistic regression was used to assess the association of sexual orientation with three types of victimisation (verbal abuse, physical abuse and feeling threatened by a person intoxicated on alcohol in the last 12 months) and controlled for probable confounding variables. Results - Of 24,858 eligible respondents aged 14 years or older, 26.8% experienced victimisation. Less than 30% of heterosexual men and women suffered victimisation compared with nearly 50% of gay men and bisexual women. Controlling for alcohol, tobacco and illicit drug use, age group, mental health, Indigenous status and socioeconomic factors, logistic regression, stratified by gender, found that the odds of both verbal [adjusted odds ratio (AOR) = 1.52] and physical abuse (AOR=2.04) were greatest for lesbians, while gay men had the greatest odds (AOR=2.25) of feeling threatened. Discussion and Conclusions - Across all types of victimisation, some or all sexual minority groups had increased odds of being victimised in the last 12 months compared with their heterosexual counterparts. The pattern of results shows the importance of disaggregating sexual minority status in considering the impact of alcohol-related victimisation and in developing interventions or policies.